Structure and Property Changes of Transglutaminase-Induced Modification of Sodium Caseinate in the Presence of Oligochitosan of 5 kDa. Issue 11 (1st November 2016) - Fu, Miao; Zhao, Xin-Huai
Abstract : Sodium caseinate was modified by transglutaminase-catalyzed reaction in the presence of oligochitosan of 5 kDa at two different levels, aiming to generate two glycated and crosslinked caseinate products (GC-caseinate I and II) and to clarify their respective structure and property changes. Electrophoretic analysis with aid of protein and saccharide staining confirmed that both GC-caseinate I and II were glycated and crosslinked protein products, while high-performance liquid chromatrography analysis demonstrated that both GC-caseinate I and II contained glucosamine (12.8 and 30.8 g/kg protein, respectively). In comparison with sodium caseinate, GC-caseinate I and II also contained less reactable –NH2 groups (0.50 and 0.52 versus 0.62 mol/kg protein), more –OH groups in their molecules, but they had more ordered secondary structure than sodium caseinate. In addition, GC-caseinate I and II showed higher water-binding capacity, larger hydrodynamic radius (173.9 and 168.2 versus 145.3 nm), and larger negative zeta-potential (–32.9 and –30.9 versus –27.6 mV) in aqueous dispersions, but they exhibited lower thermal stability (namely, greater mass loss) at temperature higher than 286ºC. Oligochitosan-glycated sodium caseinate at lower and higher extents was observed to be unfavorable and favorable to the in vitro digestibility of GC-caseinate I and II, respectively. It is concluded that application of transglutaminase and the oligochitosan can modify structure and property of sodium caseinate to generate new protein ingredients with good hydration and colloidal stability.